2002
DOI: 10.1021/ja027552x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene·Pyrene Complexes at the Active Site of Cytochrome P450 3A4:  Evidence for a Multiple Substrate Binding Site

Abstract: Cytochrome P450 monooxygenases (CYPs) metabolize nearly all drugs and toxins. Recently, it has become clear that CYPs exhibit both homotropic and heterotropic allosteric kinetics for many substrates. However, the mechanism of cooperative kinetics has not been established for any specific human CYP/substrate combination. Suggested mechanisms include binding of multiple substrates within distinct, static, subsites of a single large active site or binding of multiple substrates within a single fluid active site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 19 publications
1
63
1
Order By: Relevance
“…Interestingly, the active site of P450 3A4 is known to be very large (20,21,29). Interactions among multiple ligands have been invoked as a mechanism for cooperativity with P450 3A4 (11), and stronger fluorescence evidence for the presence of pyrene excimers in the protein has been presented (73). However, in the 1-hydroxylation of pyrene by P450 3A4 only weak homotropic cooperativity was observed, with an apparent Hill coefficient (n) of ϳ1.7 in some cases, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the active site of P450 3A4 is known to be very large (20,21,29). Interactions among multiple ligands have been invoked as a mechanism for cooperativity with P450 3A4 (11), and stronger fluorescence evidence for the presence of pyrene excimers in the protein has been presented (73). However, in the 1-hydroxylation of pyrene by P450 3A4 only weak homotropic cooperativity was observed, with an apparent Hill coefficient (n) of ϳ1.7 in some cases, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence spectroscopy has been successfully exploited by several labs to probe the various putative binding sites of CYP3A4 [10,12,16,17,22,40]. Some studies have utilized hemedependent quenching of fluorophores to measure ligand binding and to monitor putative conformational changes [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Most models used to explain the cooperativity of this enzyme have relied on the postulate that multiple ligands bind simultaneously to the enzyme [8,14,15], although direct confirmation of the specific location of binding sites has been challenging. Spectroscopic studies [16,17] and recently published X-ray crystal structures [18] have suggested that multiple ligand binding within the CYP3A4 active site is possible, as is binding at a remote site on the protein surface. However, allosteric kinetics could be observed, even in the absence of multiple ligand binding, if kinetically distinct conformations are not in rapid equilibrium [19,20].…”
mentioning
confidence: 99%
“…Although most analysis of P450 cooperativity has been based on steady-state kinetics of substrate oxidation, more recent attention has focused on investigating the substrate binding step in the CYP3A4 catalytic cycle [20,[40][41][42][43][44][45][46][47][48][49]. In general, cooperativity in substrate binding is revealed by a sigmoidal curve of the substrate-induced displacement of the spin equilibrium of the heme iron, which is known to be an important determinant of the catalytic efficiency and coupling of cytochromes P450 [50][51][52].…”
Section: Introductionmentioning
confidence: 99%